2009
DOI: 10.1007/s12555-009-0617-6
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive fuzzy IMM algorithm for uncertain target tracking

Abstract: In real system application, the interacting multiple model (IMM)-based uncertain target tracking system operates with the following problems: it requires less computing resources as well as a robust performance with respect to the maneuvering such as a sub-model mismatched case, and further, it requires an easy design procedure related to its structures and parameters. To solve these problems, an adaptive fuzzy IMM (AFIMM) algorithm, which is based on well-defined basis sub-models and well-adjusted mode transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The IPSRE performance was verified with the PSR estimation problem that the revolution velocity of the propeller shaft is time-varying, based upon the frequency spectrum produced from tracking [12] the passive sonar target. Although this simulation and verification has been previously studied in [7], this case study was more concrete because it had a greater variety in conditions and results.…”
Section: Simulation Resultsmentioning
confidence: 98%
“…The IPSRE performance was verified with the PSR estimation problem that the revolution velocity of the propeller shaft is time-varying, based upon the frequency spectrum produced from tracking [12] the passive sonar target. Although this simulation and verification has been previously studied in [7], this case study was more concrete because it had a greater variety in conditions and results.…”
Section: Simulation Resultsmentioning
confidence: 98%
“…To assess the proposed RIMM-UKF algorithm under modeling uncertainty, two CT models corresponding to different turn rates are used, that is, −1 rad/s and 0 rad/s. As the turn rate of the CT model approaches zero, it can be regarded as an approximation of the UM model [43]. However, two CT models corresponding to different turn rates do not exactly match the true navigation trajectory, as shown in Fig.…”
Section: B Evaluationmentioning
confidence: 99%
“…In application, the parameter optimization is a problem which need to be solved. The researchers [7,13] have used particle swarm optimization and genetic algorithms to search the parameters of CPG. Then the swarm intelligence algorithms are effective methods to solve this problem.…”
Section: Parameters Optimization Of the Cpg Modelmentioning
confidence: 99%
“…The researchers found that the swarm intelligence algorithms are effective methods to solve the parameters optimization. Kim et al [7] used nonparametric estimation based particle swarm optimization to search the parameters of CPG. In the swarm intelligence algorithms, the bat algorithm is a new algorithm and it is applied in many optimization problems [8,9].…”
Section: Introductionmentioning
confidence: 99%